2019
DOI: 10.1007/s00464-019-07021-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of surgical payer costs and implication on the healthcare expenses between laparoscopic magnetic sphincter augmentation (MSA) and laparoscopic Nissen fundoplication (LNF) in a large healthcare system

Abstract: Introduction Magnetic sphincter augmentation (MSA) is a promising antireflux surgical treatment. The cost associated with the device may be perceived as a drawback by payers, which may limit the adoption of this technique. There are limited data regarding the cost of MSA in the management of reflux disease. The aims of the study were to report the clinical outcome and quality of life measures in patients after MSA and to compare the pharmaceutical and procedure payer costs and the disease-related and overall e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In addition, there was a trend toward lower overall medical expenses and costs related to PPI use after MSA compared with LNF. 35 Although MSA was associated with a higher procedural payer cost compared with LNF, the payer costs might be offset due to reductions in the expenses after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, there was a trend toward lower overall medical expenses and costs related to PPI use after MSA compared with LNF. 35 Although MSA was associated with a higher procedural payer cost compared with LNF, the payer costs might be offset due to reductions in the expenses after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…Operation cost: The costs of the operations for patients were the median costs obtained from the literature [ 17 , 18 ].…”
Section: Methodsmentioning
confidence: 99%
“… 49 Further, a prospective observational study comparing MSA and laparoscopic Nissen fundoplication found that at 12 months after surgery, reimbursement for medical expenses decreased by 11% for MSA and 1% for laparoscopic Nissen fundoplication compared with preoperative reimbursement. 50 …”
Section: Outcomes Compared With Fundoplicationmentioning
confidence: 99%